Development of the smartphone application for patients with dementia: a literature review - Utami, Pinasti; Rahmawati, Fita; Astuti; Zullies Ikawati (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
Primary technological developments are advancing rapidly, and dementia patients and caregivers are becoming more open to online interactions for enhancing dementia care. However, most existing applications only focus on patients, and there is a need to expand their scope to include caregivers. Ideally, the application should be designed with the caregiver in mind, and considering the impact they experience while caring for dementia patients. Families are specifically targeting caregivers who are at the highest risk of experiencing caregiver burnout, such as those caring for patients. This literature review described the necessary functions and content for dementia caregivers, serving as a reference for designing, developing, and implementing smartphone solutions that meet user needs. This review utilized articles from three databases i.e. PubMed NCBI, ScienceDirect, and Tandfonline. The Boolean approach method was used to generate the exact keywords. The inclusion criteria for this study encompassed smartphone applications for dementia patients, focusing on function and content, published in English-language journals within five last years, with an emphasis on original research and free full access. In this review, six articles were obtained. From these six articles, four findings related to functions and content were identified i.e. education, interactive health promotion, interaction stakeholder, and referencing information sources. These four aspects could serve as references for developing comprehensive smartphone applications for caregivers, and facilitating integrated health care.